2002
DOI: 10.1089/107662902760190617
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Barriers to Quinolone Resistance inStreptococcus pneumoniae

Abstract: It is assumed that bacteria always pay a significant physiological price for the acquisition of resistance to antibiotics. To test whether this was the case for a strain of Streptococcus pneumoniae that develops resistance to fluoroquinolone antibiotics, we selected resistance to these agents in a wild-type strain and measured their fitness in comparative growth experiments. The relative growth rate of a mutant strain selected on ciprofloxacin (parC Serine 79 to Tyrosine) was compared with its susceptible isog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
47
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 37 publications
3
47
0
Order By: Relevance
“…Third, we constrained our parameter sets to a set of scenarios with very low fitness costs, to ensure that it was possible for high-level resistance to spread. Although there are no quantitative estimates of fitness costs for fluoroquinolone resistance, it seems possible that the costs are higher than the values considered here (36,37), meaning that the actual probability for using newer fluoroquinolones without exten- Typical and atypical results are presented as mean (SD). *Typical results of highest Resistance occur with immediate switch, whereas atypical results occur with delayed switch.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Third, we constrained our parameter sets to a set of scenarios with very low fitness costs, to ensure that it was possible for high-level resistance to spread. Although there are no quantitative estimates of fitness costs for fluoroquinolone resistance, it seems possible that the costs are higher than the values considered here (36,37), meaning that the actual probability for using newer fluoroquinolones without exten- Typical and atypical results are presented as mean (SD). *Typical results of highest Resistance occur with immediate switch, whereas atypical results occur with delayed switch.…”
Section: Discussionmentioning
confidence: 97%
“…The wide clonal spread of highly resistant strains (33) suggests that these strains are not much compromised in their fitness and are capable of spreading. The existence of fit, highly resistant strains may imply compensatory chromosomal changes (34,35), because animal studies showed pneumococcal strains as being greatly compromised in vivo upon acquisition of high-level resistant alleles (36,37). These characteristics suggest that, in the case of amoxicillin, the policy that maximizes treatment success (widespread use of higher doses) may unfortunately foster the emergence of higher-level resistance at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have investigated the fitness of antimicrobial-resistant pathogens (8,34,35) and antimicrobial-resistant S. pneumoniae (6,7,36,37), few have investigated the fitness of fluoroquinolone-resistant bacteria (4,5 (5), who demonstrated that clinical strains of QRSP were less virulent in outbred mice than a quinolone-susceptible laboratory strain and its quinolone-resistant isogenic mutant. If QRSP are less efficient than fluoroquinolone-susceptible S. pneumoniae at colonizing humans, the result could explain the few reports of clonal lineages of QRSP.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, antimicrobial resistance in a pathogen may come at a cost: modifications that allow survival in the presence of antimicrobial drugs may render the pathogen less efficient at host infection, even in the absence of the antimicrobial agent (3). Little is known about the fitness of antimicrobial-resistant S. pneumoniae (4)(5)(6)(7)(8). The emergence of quinolone-resistant S. pneumoniae (QRSP) appears to be more dependent on fluoroquinolone selection of de novo spontaneous point mutations in the quinolone resistance-determining regions (QRDRs) of the topoisomerase genes gyrA and parC than on clonal dissemination (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…How fluoroquinolone resistance is linked to loss of beta-hemolysis and papEF is not obvious. It has been proposed that fluoroquinolone-resistant bacteria may be less fit than susceptible isolates due to decreased efficiency of gyrase and topoisomerase (5,12). In contrast, the development of resistance to ampicillin has been correlated to the presence of the Dr adhesin, which plays a role in colonization and invasion of the host (6).…”
mentioning
confidence: 99%